Belarus Systematic Country Diagnostic : Towards a Competitive, Inclusive and Dynamic Belarus - World Bank Group (World Bank, Washington, DC, 2018)
Since the collapse of the Soviet Union, Belarus has pursued a gradual transition path characterized by slow opening of the economy to the private sector and a limited reform of the governance system of state-owned enterprises (SOEs). This systematic country diagnostic (SCD) demonstrates that there is a window of opportunity to proactively lay down foundations towards a new vision - a competitive, inclusive, and dynamic Belarus. At the core of this new vision is managing a transition to a new growth path that is sustainable and inclusive. The SCD has identified seven key priorities for achieving further progress towards the twin goals in Belarus. The report is structured as follows: chapter one describes trends in poverty reduction and in shared prosperity and examines the conjecture that economic growth was the main determinant of improvements in income distribution. Chapter two analyzes the sustainability of economic growth and income distribution gains. Chapter three sketches a vision of socio-economic development for Belarus in the next decade and formulates three pathways towards the sustainable and inclusive growth of an internationally competitive economy. Chapter four describes priority actions to achieve that vision.